2022
DOI: 10.1108/rbf-10-2021-0218
|View full text |Cite
|
Sign up to set email alerts
|

Time-varying herding spillover for emerging countries: evidence from BRIC countries and Turkey

Abstract: PurposeThis study aims to investigate herding spillover in BRIC (Brazil, Russia, India and China) countries and Turkey under different regimes by using a time-varying approach.Design/methodology/approachThe authors used the structural change model of Bai and Perron (1998).FindingsThe results indicate that there is an evidence of herding behaviour in the Chinese stock market in two different regimes. These regimes cover the recent global financial crisis and the period of Hong Kong protests. We also report the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…For this reason, we collected the 200 individual stocks data along with market index. We used the approach of CSAD developed by Yasir and € Onder (2023) and augmented by Putra et al (2017) to investigate the time varying nature of herding behavior. In order to investigate the break points in our data set of UK stock market, we used the approach of Christie and Huang (1995), Putra et al (2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason, we collected the 200 individual stocks data along with market index. We used the approach of CSAD developed by Yasir and € Onder (2023) and augmented by Putra et al (2017) to investigate the time varying nature of herding behavior. In order to investigate the break points in our data set of UK stock market, we used the approach of Christie and Huang (1995), Putra et al (2017).…”
Section: Discussionmentioning
confidence: 99%
“…In the recent literature of herding behavior, Spillover of herd anomaly has gained an increasing interest of researchers. Yasir and € Onder (2023) investigate the herding spillover among BRIC, Turkey and US using the structural break approach and reported significant evidence of herding spillover among the targeted stock markets.…”
Section: Investigation Of Herding Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Studies include BRICS countries with similar emerging countries in the analysis. We include T€ urkiye in the analysis due to its high growth potential, young population, geopolitical importance and being an important energy hub (Bacik, 2013;Yildirim et al, 2022;Yasir and € Onder, 2023). GG is a proxy of the dependent variable.…”
Section: Financial Determinants Of Green Growthmentioning
confidence: 99%
“…For instance, Fang et al (2021) found that the COVID-19 pandemic strengthens the effect of stock markets on herding behavior and reinforces the spillover effect of regional herding on herding behavior. Meanwhile, Yasir and € Onder (2022) showed that under two different regimes, there is herding behavior in the Chinese stock market. They showed also that in times of crisis, there is a cross-border spillover between Brazil and India.…”
Section: Introductionmentioning
confidence: 99%